KONSTRUKSI MODEL PENCEGAHAN FRAUD MELALUI RED FLAG BASED SYSTEM DI PEMERINTAH KABUPATEN JEMBER (STUDI KASUS DI INSPEKTORAT KABUPATEN JEMBER): (CONSTRUCTING FRAUD PREVENTION MODEL THROUGH RED FLAG-BASED SYSTEM IN THE JEMBER REGENCY GOVERNMENT (A CASE STUDY OF THE JEMBER REGENCY INSPECTORATE)) - Andriana, Andriana; Kurrohman, Taufik; Putra, Hendrawan Santosa; Mulyono, Resha Dwi Ayu Pangesti (UPT Penerbitan Universitas Jember, 2024)
This research aims to present a system that can prevent fraud in the form of compliance and internal control within the Jember Regency Government through a red flag-based system. The study uses a qualitative case study method. The Inspectorate currently requires indicators to prevent the occurrence of fraud. The techniques employed to collect data include observation, interviews, and documentation. The results indicate that all Regional Device Organizations (OPD) in Jember Regency analyze various risks. These risks will be further analyzed for their root causes and the impacts they may generate. Based on the risk map that has been created, there are a total of 412 risks identified across 72 Regional Device Organizations (OPD) in Jember Regency. The focus of the risks with potential fraud in this study lies within the category related to finance (finance risk). Specifically, there are 33 financial-related risks identified across all Regional Device Organizations (OPD) in Jember Regency.